Fibrosis-4 Index Is Closely Associated with Arterial Damage and Future Risk of Coronary Heart Disease in Type 2 Diabetes. (7th July 2022) - Watanabe, Kentaro; Takakubo, Noe; Saigusa, Taro; Nagasawa, Akiko; Yamana, Midori; Ojima, Midori; Kameda, Wataru; Susa, Shinji; Ishizawa, Kenichi; Ishihara, Hisamitsu
Abstract : This study evaluated the association between fibrosis-4 (FIB 4) index and arterial damage or future risk of coronary heart disease (CHD) in type 2 diabetes. The study subjects were 253 patients with type 2 diabetes. The FIB4 index, as a marker of hepatic fibrosis based on age, aspartate aminotransferase and alanine aminotransferase levels, and platelet count, was calculated for all subjects. Carotid intima-media thickness (IMT), carotid artery calcification (CAC), and aortic arch calcification (AAC) grade (0–2) were assessed as atherosclerotic variables. The Suita score was calculated as the future risk of coronary heart disease (CHD). We assessed whether the FIB4 index was associated with both atherosclerotic variables and the Suita score. FIB4 index was significantly associated with IMT ( r  = 0.241, P < 0.001 ) and Suita score ( r  = 0.291, P < 0.001 ). Subjects with CAC showed a significantly higher FIB4 index score compared to subjects without (1.70 ± 0.74 and 1.24 ± 0.69, respectively, P < 0.001 ), whereas the FIB4 index was significantly elevated with a higher grade of AAC (1.24 ± 0.74, 1.56 ± 0.66, and 1.79 ± 0.71, respectively, P < 0.001 ). Linear regression analysis adjusted for clinical characteristics indicated that the FIB4 index was positively associated with IMT, Suita score, CAC, and AAC grade ( β  = 0.241, P = 0.004 ; β  = 2.994, P < 0.001 ; β  = 0.139, P = 0.001 ; and β  = 0.265, P < 0.001, respectively). FIB4 index is closely associated with arterial damage and future risk of CHD in type 2 diabetes.